CHRONIC DIZZINESS POST TRAUMATIC BRAIN INJURY: A CROSS-SECTIONAL STUDY. Issue 12 (15th November 2016) - Ahmad, Hena; Arshad, Qadeer; Roberts, Richard; Patel, Mitesh; Ham, Timothy; Sharp, David; Seemungal, Barry
Abstract : Traumatic brain injury is the commonest cause of disability in young adults. Chronic dizziness and imbalance are amongst the commonest causes for post-traumatic morbidity (up to half of patients at 5 years). These symptoms significantly impair quality of life and are also an independent predictor of failure to return to work post-TBI. The reasons underlying chronic dizziness post TBI, however, remain unexplained. 20 consecutive TBI patients (12M, mean=44.7 yrs range 19–69) with persisting dizziness (>6 months post-TBI, range 6–18 months) underwent comprehensive clinical and vestibular laboratory testing (full electronystagmography, vestibular-evoked myogenic potentials, smooth pursuit (0.1–0.4 Hz), VOR (vestibulo-ocular reflex) suppression (0.25 Hz, 40 o/sec); and optokinetic stimulation (40 o/s) at a tertiary neuro-otology centre. The two commonest causes of post-TBI dizziness were benign positional paroxysmal vertigo (n=8) and vestibular migraine (n=4) and 40% of our sample had both diagnoses (n=8). Central vestibular dysfunction as evidenced by impaired VOR suppression and broken pursuit (gain <0.40) was found in 30%. TBI results in multiple, albeit treatable, vestibular diagnoses, with a combination of central and peripheral dysfunction, hence a thorough evaluation is required to detect all potential diagnoses. The disruption of central vestibular pathways post TBI may lead to impairment of brain plasticity repair mechanisms.